Aplikasi IRT dalam Analisis Aitem Tes Kognitif - Firmanto Adi Nurcahyo (Faculty of Psychology Universitas Gadjah Mada, 2016)
Item Response Theory (IRT) was developed to overcome the problems in Classical Test Theory (CTT). Item analysis using IRT is based on the parameters used which are item difficulty, item discrimination, and pseudo-chance level. This paper aims to provide an overview of how IRT isused to perform item analysis on cognitive tests. Simulation data of seven items with 900 subjects were used . IRT analysis was performed with R Program based on one, two, and three-parameter logistic model. The results were then discussed